Efeitos em curto prazo das variáveis climáticas sobre a revoada de alados de térmitas capturados por armadilhas não atrativas - Lucena, Emanuelly Félix de (2019)
Termite alates are the main responsible for the rising of new colonies and the increasing of species area. The termites’ swarm are a result of several complex behavioral responses that are influenced by regional weather patterns. In view of this, the aim of this study was to make a correlation between the occurrence of these swarming events and climatic variables at the Caatinga region, Paraiba State, Northeast of Brazil. The alates sample was made by using 40 trays distributed in one transect of 2.300 meters, during 12 months. To avoid multicollinearity between the predictor variables, a PCA (Principal Component Analysis) was made with 12 meteorological variables, which five were selected. The analysis was made in consecutive 40 days, for family and subfamily: Rhinotermitidae and Termitidae (Apicotermitinae, Nasutitermitinae and Termitinae), using the GLM (Generalized Linear Model). The flights of Apicotermitinae had a negative relation with the air density. The swarming occurred from December 2017 to April 2018. Atmospheric pressure, soil moisture, temperature and air density had significant effects in swarming events, according to each group. Rhinotermitidae swarmed mainly as a consequence of the atmospheric pressure decrease, while majority of Termitidae as a consequence of lower temperature and intermediate values of soil moisture. Apparently, the termites’ swarm occurred because of the influence of environmental complex variables that, in synergism or in isolation, generated more favorable conditions for the occurrence of swarms.